PARENTAL BONDING TOWARDS CHILDREN AND ITS AFFECT ON CHILDREN’S SELF-ESTEEM AND SELF-EFFICACY (Proceedings of the International Conference on Social Sciences, 2018)
The study intended to study the relationship between parental bonding and its effect on children’s self-esteem and self-efficacy in both girls and boys. To conduct the study a sample of 100 boys and 100 girls from different schools through convenience sampling. The Parental Bonding Scale, Rosenberg Self Esteem Scale and General Self Efficacy scale were used in the research. This research highlights the impact of parental bonding on the self-esteem and self-efficacy of children. It shows that there exists significant effect of parental bonding on self-efficacy, but it does not have a significant effect on self-esteem. Boys reported slightly higher self-esteem than girls, but there is no difference between boys and girls on self-efficacy. Our research also reported that boys have a slightly higher parental bonding than females. Among the demographic variables, family structure was found to be non-significant to predict self-esteem and self-efficacy. The study also confirms that parental bonding is significantly related to age. These findings confirmed the need of considering multidimensional aspects of parental bonding and the different perspective in explaining the parental impacts on children self-efficacy and self-esteem.
Keywords: Self-esteem, Self-efficacy; Parental bonding